The Effect Of Oxidation Treatment Of Mwcnt On The Properties Of Pdms Nanocomposite - Mazlan, Norkhairunnisa (2012)

(untitled)
MWCNT have a unique electrical properties, thermal conductivity which is higher than diamond and a good mechanical properties where strength and stiffness exceed any other current materials However, poor dispersibility and interfacial adhesion of MWCNT in polymer matrix presents a considerable challenge in developing nanocomposite with good properties. Oxidation treatment was done on MWCNT as to improve the dispersion and interfacial adhesion between the nanotubes and PDMS. The oxidation treatments of MWCNT were carried out by oxidizing using either single acid (HNO3) or mixture of acids (HNO3/H2SO4) at 3:1 ratio. The treatments were done for different period of time (3 and 6 hours) and temperature (80°C and 140°C). FTIR and XPS analysis showed the presence of various functional groups such as C-O, C=O and COOH. The O/C ratio increased from 0.17 for untreated MWCNT to 0.56 for oxidized MWCNT. Acid bes titration showed increase in concentration of acid groups about 159%. The oxidation affects the tubes more significantly when the temperature and time increased to 140°C and 6 hours respectively as the ID/IG ratio increased from 0.19 to 0.83 and reduction in thermal stability. The presence of functional groups formed electrical double layer on the MWCNT surface and thus, gave good dispersibility in water. This layer also overcome the strong van der Waals force within the nanotubes and reduced agglomeration. The presence of defects and catalysts were also observed by TEM. For PDMS filled with MWCNT oxidized in HNO3 at 80°C for 3 and 6 hours, the tensile strength increased to 5.06 MPa, while thermal and electrical conductivity slightly increased for approximately to 24% and 42%, respectively over the untreated MWCNT/PDMS nanocomposites. However, for PDMS filled with MWCNT oxidized at 80°C for 6 hours in acid mixture, the thermal and electrical conductivities were slightly decreased to 0.19 W/mK and -4.62 Log/Scm-1. Decrease in properties was more significant for PDMS filled with MWCNT oxidized at 140°C for 6 hours as the Tg value decreased for 9°C compared PDMS reinforced with MWCNT oxidized at 80°C for 6 hours, in which its Tg was approximately -35°C. Aggressive oxidation treatment reduces the capability of MWCNT to form good interfacial interaction with the PDMS matrix. However, this type of MCWNT was suitable to be used to increase the plasticity of the polymer matrix.